(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Mrs. Indumathy Vemanna, Assistant Professor, PG & Research Department of Biochemistry, Theivanai Ammal College for Women(A), Villupuram, Tamil Nadu, India Abstract Disease management applies comprehensive, evidence-based approaches to optimize medication therapy across major therapeutic areas through systematic assessment, intervention, and monitoring strategies. Cardiovascular disorder management encompasses hypertension, dyslipidemia, heart failure, anticoagulation, and coronary syndromes through guideline-directed medication selection, risk stratification, and monitoring protocols addressing both symptomatic control and outcome modification. Endocrine disorder approaches optimize diabetes mellitus, thyroid conditions, adrenal disorders, and metabolic bone diseases through medication regimen individualization, monitoring parameter selection, and complication prevention strategies addressing complex hormonal interactions. Respiratory condition management addresses asthma, COPD, pulmonary infections, and sleep-disordered breathing through appropriate controller and rescue medication selection, device technique optimization, and exacerbation prevention protocols. Infectious disease therapy implements antimicrobial stewardship principles, empiric therapy selection, de-escalation protocols, and transition strategies across bacterial, viral, and fungal infections balancing effective pathogen eradication with resistance prevention. Oncology management encompasses chemotherapy optimization, targeted therapy selection, immunotherapy monitoring, and supportive care integration through molecular biomarker utilization and complex regimen management. Mental health approaches address depression, bipolar disorder, schizophrenia, anxiety, and substance use disorders through appropriate medication selection, therapeutic monitoring, and adherence support addressing both symptomatic control and functional improvement. This systematic approach enables optimal medication management across diverse disease states through specialized therapeutic knowledge and patient-centered application. Keywords: Pharmacotherapeutics, Guideline Implementation, Therapy Optimization, Disease Modification, Treatment Algorithms VIEW PDF